ฟลูแก๊สดีซัลเฟอไรเซชันโดยใช้หินปูนระหว่างการเผาไหม้ถ่านหิน - ภาคภูมิ ยินดีสิทธิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
Coal desulfurization during combustion using limestone has been studied under various reaction conditions. The effects of calcium per sulfur mole ratio in mixed sample of coal and limestone, combustion temperature, coal size and initial sulfur content in coal on percent sulfur content in ash and desulfurization efficeincy were investigated and the consumption of the mixed fuel of biomass fuel, coal and limestone was also compaired. The X-Ray fluorescence technique was used to monitor the sulfur content in coals and ashes. The results showed that the mole ratio of calcium and sulfur had a significant effect. At optimum condition, the percent sulfur content in ash reached  89.3 % at calcium per sulfur mole ratio of 1.93 : 1 , temperature of 850 ºC and coal size of 0.5 - 2.0 mm. The percent sulfur content in ash slightly decreased with increasing initial sulfur in coal and was above 90 %. In addition, the percent sulfur content in ash and desulfurization efficeincy were increased when the biomass (at 10 % wt) was mixed with coal and limestone in combustion.